2013
DOI: 10.1071/rd12159
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to bisphenol A results in a decline in mouse spermatogenesis

Abstract: Bisphenol A (BPA), a chemical used in many consumer products, interferes with the endocrine system of mammals, including humans. The aim of the present study was to investigate the effect of BPA on spermatogenesis and semen quality. The objective of this study was to assess the effects of BPA on mouse spermatogenesis. CD1 mice were used in all experiments. Mice were treated with different doses of BPA (0, 20 and 40 μg kg⁻¹ day⁻¹ from postnatal Day (PND) 3 to PND21, PND 35 or PND49. After 5 weeks BPA treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 64 publications
2
24
0
3
Order By: Relevance
“…It was demonstrated that DNMT1, DNMT3a and DNMT3b are robustly expressed in the early embryonic stage; however, the biological functions of DNMT2 remain elusive (23-25). (26)(27)(28)(29)(30), predominantly methylates hemimethylated CpG dinucleotides in the genome, and is considered to be the key maintenance methyltransferase during cell division (29)(30)(31)(32)(33). The DNMT2 gene is the most highly conserved of the methyltransferases in eukaryotes, and has been identified in organisms that exhibit DNA methylation, as well as in those that do not (26)(27)(28)(29)(30).…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that DNMT1, DNMT3a and DNMT3b are robustly expressed in the early embryonic stage; however, the biological functions of DNMT2 remain elusive (23-25). (26)(27)(28)(29)(30), predominantly methylates hemimethylated CpG dinucleotides in the genome, and is considered to be the key maintenance methyltransferase during cell division (29)(30)(31)(32)(33). The DNMT2 gene is the most highly conserved of the methyltransferases in eukaryotes, and has been identified in organisms that exhibit DNA methylation, as well as in those that do not (26)(27)(28)(29)(30).…”
Section: Dna Methylationmentioning
confidence: 99%
“…DNMT3a and DNMT3b primarily perform de novo methyl transfer reactions via interactions with transcriptional repressors. They are considered to differ mechanistically due to inherent differences in their catalytic domains, and it has been suggested that DNMT3a is distributive while DNMT3b is processive (31)(32)(33)(34)(35)(36). The third significant member in the DNMT3 family is DNMT3L, which is considered to be required for the establishment of maternal imprints in oocytes (37)(38)(39)(40)(41), and has also been shown to be expressed during spermatogenesis (37,(42)(43)(44).…”
Section: Dna Methylationmentioning
confidence: 99%
“…53 Meanwhile, postnatal exposure to lower BPA doses relevant to human exposure (20 and 40 μg/kg/day from day 3) resulted in slowed meiotic progression of germ cells after 5 wk treatment along with decreased quality and quantity of spermatozoa in 7-wk-old mice. 54 …”
Section: Bpa Exposure and Testis Developmentmentioning
confidence: 99%
“…DEHP has been identified as an endocrine disruptor in the endocrine system and disrupts the physiological function of endogenous hormones to induce a range of problems in the body (Doyle et al 2013;Zhang et al 2013bZhang et al , 2013cZhang et al , 2014b. A series of animal studies have revealed the reproductive toxicity of DEHP, such as decreasing sperm production, inducing infertility, affecting ovarian follicle development (Zhang et al 2013a(Zhang et al , 2013b(Zhang et al , 2013c and causing dramatic changes in germ cells (Bromer et al 2010;Zhang et al 2013bZhang et al , 2013cZhang et al , 2014b. Using in vivo and in vitro models, our previous studies have demonstrated that DEHP has many negative effects on oogenesis and primordial-follicle assembly, especially when the DEHP exposure occurs at the early postnatal stage (Zhang et al 2013b(Zhang et al , 2013c; however, whether maternal DEHP exposure affects fetal ovarian development has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%